A novel bio-inspired multi-joint anti-vibration structure and its nonlinear HSLDS properties. (April 2020) - Jiang, Guoqing; Jing, Xingjian; Guo, Yingqing
Highlights: A novel bio-inspired multi-joint anti-vibration structure is proposed and systematically studied. . The structure is obtained by mimicking muscle-joint structure and skeleton of animal legs. Ultra low resonant frequency can be obtained in a larger working range without losing loading capacity. Appropriate parameter setting leads to excellent high-static-low-dynamic stiffness property. This unique vibration isolation structure can be more compact and flexible in implementation. Abstract: A unique bio-inspired multi-joint leg-like or limb-like vibration isolation structure is studied by mimicking the skeleton and joint structures of animal legs, and its advantage in passive vibration isolation is systematically investigated. This bio-inspired structure uses several small quadrilateral structures composed by short adjustable rods and a transverse spring to simulate the multi-articulation of animal legs and adopts long rods to simulate the skeleton. The equivalent static stiffness property, loading capacity and dynamic vibration isolation performance of the structure are systematically studied. It is shown that the nonlinear stiffness characteristics of the structure can lead to very excellent vibration isolation capability in the low-frequency band. Different from many existing quasi-zero-stiffness (QZS) isolators in the literature, this novel anti-vibration structure can demonstrate superior high static but low dynamic stiffness (HSLDS) property and thus excellent vibration isolation performance, subject to large vibration amplitude. Through adjusting proper structural parameters including the rod-length, assembly angle, spring stiffness and layer number according to the influence of the structural parameters on the nonlinear stiffness property, the new structure can have the optimal vibration isolation performance without sacrificing its loading capacity to meet actual requirements. Especially, the length of long rods which is used to simulate the skeleton can be adjusted to obtain better vibration isolation performance than adjusting other parameters, followed by the adjustment of the parameters of small quadrilateral structures. The analysis of the influence of structural parameters on the vibration isolation performance shows that the symmetry between different layers has an important role in maintaining the characteristic of the HSLDS. The comparison with other existing vibration isolation structures of the QZS property also indicates that, the new vibration isolation structure can have a better vibration isolation performance with relatively a smaller size of the overall structure. Experiments are successfully conducted and validated the beneficial nonlinear properties of the structure. This novelbio-inspired anti-vibration structure would have great advantages in practical engineering applications.